Removal of Cr(VI) from aqueous solutions by activated carbon and its composite with P2W17O61: A spectroscopic study to reveal adsorption mechanism - Abdul G. Al Lafi; Ali Khuder (Heliyon)
Molecular scale information is needed to understand ions coordination to mineral surfaces and consequently to accelerate the design of improved adsorbents. The present work reports on the use of two-dimensional correlation Fourier Transform infra-red spectroscopy (2D-COS-FTIR) and hetero 2D-COS-FTIR- X-ray diffraction (XRD) to probe the mechanism of Cr(VI) removal from aqueous solutions by activated carbon (AC) and its composite with P2W17O61 (AC-composite). The adsorption data at an initial Cr(VI) concentration of 320 mg L−1 (320 ppm) revealed maximum adsorption capacities of 65 mg g−1 for AC and 73 mg g−1 for AC-composite, corresponding to removal percentages of 83 % and 94 %, respectively. The adsorption mechanism of Cr(VI) onto AC involved electrostatic attraction of charged ions, reduction of Cr(VI), orientation of O-H groups, complex formation and ion exchange reaction. On the other hand, ion exchange reactions were not observed in the case of AC-composite, but increasing reduction and complex formation due to the presence of W were more pronounced. Moreover, a monosubstituted compound; i.e. K6P2CrW17 O61·nH2O, having chromium in its maximum oxidation state (Cr(VI)) was formed. These resulted in an improved adsorption capacity of AC-composite towards Cr(VI) in comparison to AC, and could explain the differences in adsorption thermodynamics and capacity of the two studied adsorbents. High value information could be extracted from both FTIR spectroscopy and XRD patterns when combined with available 2D-COS routines and subsequently powerful tools to investigate the mechanisms of adsorption are obtained.